Melihat Kebijakan Penanganan Covid-19 yang Populer di Kalangan Masyarakat Aceh - Saddam Rassanjani; Helmi Helmi; Minawati Lingga (Pencerah, 2022)
The Aceh government has deployed several programs and policies in tackling the global disaster of COVID-19. Still, there is currently no sign that the community can fully breathe a sigh of relief and say goodbye to Corona. This study aims to look at people's perception of policies or programs from the government in handling COVID-19 in Aceh Province. The research method used to answer research questions here is a mixed-methods approach, i.e., quantitative through survey and qualitative through literature studies. The results showed that the 4M Health protocol (Wearing Masks, Maintaining Distance, Washing Hands, Avoiding Crowds) is considered the most effective policy in reducing the spread of the COVID-19 virus according to the people's perception of Aceh. Meanwhile, the implementation of curfews in the pandemic era is considered a very unpopular program in the eyes of the people of Aceh. Apart from the pros and cons of the Acehnese people against several policy packages in handling the pandemic since 2020, the government has tried to maximize their performance in tackling COVID-19. Therefore, to achieve the government's goal in solving the COVID-19 problem from the earth of Aceh, cooperation between the government and the community is needed to support each other in fighting the virus. It is expected that the government will continue to be consistent in protecting the community from the dangers of COVID-19, and it is also expected to publish several policies and programs that can end the pandemic appropriately and quickly.